PENGEMBANGAN MEDIA DIGITAL KARTU DOMINO RANTAI MAKANAN (DORAMA) PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - Maria Erica Istyasiwi; Yetty Auliaty; Dudung Amir Sholeh (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
This study aims to develop the Dominoes card game media in the science learning of food chain material for class V SD in the form of an application and also to determine the feasibility of the Food Chain Dominoes card game media. The research method used is Research and Development or R&D. The research model used is ADDIE. Data collection instruments in the form of observations, interviews, expert test questionnaires and student response questionnaires. The expert test process is carried out to material experts, media experts and linguists. The results of the material expert test validation are 100% so it can be said to be "very feasible", the media expert test validation results are 85.5% so it can be said to be "very feasible", and the linguist test validation results are 91.6% and are said to be "very feasible".It can be averaged that the three expert test scores obtained a value of 92.3% and can be said to be "very feasible”. The student response test could on a one-to-one test consisting of 5 students who live close to the researcher. The results of the one to one test to 5 students resulted in an average of 93.5% which can be said to be a "very feasible" product. This shows that the DORAMA Card game media is feasible to be used as a medium in learning Natural Science material for Food Chain.